Iatrogenic Dissection of Left Main-Stem during Primary PCI for Inferior STEMI: A Catastrophic Complication - Kabir, CM Shaheen; Ali, M Liaquat; Khan, Saidur Rahman; Chowdhury, Mashhud Zia; Haq, M Maksumul (Ibrahim Cardiac Medical Journal, 2017)
Coronary artery dissection is a rare but well-recognized complication of coronary angiography with high morbidity and mortality rate. We present the case of a 54-year-old male who experienced iatrogenic left main-stem (LMS) dissection during transradial coronary angiography for inferior STEMI. The patient was successfully treated by prompt bail-out stenting. Intracoronary stenting is of value in stabilising the patients before emergency bypass surgery and can save lives in LMS complications. Ibrahim Card Med J 2015; 5 (1&2): 67-71